Analisis pengendalian internal persediaan barang dagang di Nehemia Mart Tahuna - Warouw , Irene Christina; Saerang, David Paul Elia; Korompis, Claudia W. M. (Manajemen Bisnis dan Keuangan Korporat, 2024)
This study aims to determine the internal control system for merchandise inventory according to the COSO framework at Nehemia Mart Tahuna. The research method used in this research is descriptive qualitative. The data used in this study is primary data with interview, documentation and observation collection techniques. The results of this study indicate that the internal control system for merchandise inventory at Nehemia Mart as a whole has not been implemented properly as there are still several internal control components that are not in accordance with the COSO framework. The main problem in this case is the owner is not firm in implementing every rule.